Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1021/tx5004003
|View full text |Cite
|
Sign up to set email alerts
|

Subchronic Toxicity and Cardiovascular Responses in Spontaneously Hypertensive Rats after Exposure to Multiwalled Carbon Nanotubes by Intratracheal Instillation

Abstract: The tremendous demand of the market for carbon nanotubes has led to their massive production that presents an increasing risk through occupational exposure. Lung deposition of carbon nanotubes is known to cause acute localized pulmonary adverse effects. However, systemic cardiovascular damages associated with acute pulmonary lesion have not been thoroughly addressed. Four kinds of multiwalled carbon nanotubes (MWCNTs) with different lengths and/or iron contents were used to explore the potential subchronic tox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 29 publications
(50 reference statements)
3
21
1
Order By: Relevance
“…For example, we have previously reported that MWCNTs with a length of 10–100 μm impaired pulmonary function [42] and induced severe cardiac ischemic/reperfusion injury after pulmonary instillation [43]. Similar results on MWCNT toxicity have been reported [4447]. However, it is being recognized that toxicity induced by carbon nanotubes is highly dependent on their length and functionalization.…”
Section: Discussionsupporting
confidence: 52%
“…For example, we have previously reported that MWCNTs with a length of 10–100 μm impaired pulmonary function [42] and induced severe cardiac ischemic/reperfusion injury after pulmonary instillation [43]. Similar results on MWCNT toxicity have been reported [4447]. However, it is being recognized that toxicity induced by carbon nanotubes is highly dependent on their length and functionalization.…”
Section: Discussionsupporting
confidence: 52%
“…For example, our earlier studies found that MWCNTs with a length of 10-100 μm impaired pulmonary function 22 and induced severe cardiac ischemic/ reperfusion injury after pulmonary instillation. 23 Similar results on MWCNT toxicity were also reported elsewhere, [24][25][26][27] such as subchronic toxicity, asbestos-like pathogenicity in mice, and airway fibrosis. In contrast, CNTs with a length shorter than 2 μm have been shown to exhibit minimal toxicity to various cell types, such as human promyelocytic leukemia (HL60) and human T-cells (Jurkat).…”
supporting
confidence: 85%
“…SW-CNTs (Li et al, 2007) and MW-CNTs (Xu et al, 2012) as well as nickel hydroxide-NPs (Kang et al, 2011) were able to accelerate the atherosclerosis progression in aortas of in vivo susceptible models. More recently, MW-CNTs were reported to induce a transient decrease in blood pressure, a long-term reduction in the heart rate as well as structural changes in large arteries in spontaneously hypertensive rats compared to healthy animals (Chen et al, 2015). These results are in line with epidemiological findings that have implicated particulate air pollution, and specifically its ultrafine size fraction, as an important contributor to morbidity and mortality from cardiovascular causes (Peters et al, 2011).…”
Section: Resultsmentioning
confidence: 99%